Petalling damage analysis of metallic plate structures under localized impact loading - a review - Nam, Pham Hoang (ASEAN engineering journal)
The main objective of this paper is to review the theoretical predictions on the petalling damage of plate structures against highly localized load. There are three existing methods to solve petalling problem. First method of Zaid and Paul (1958) used momentum conservation to calculate high speed projectile perforation of a plate structure. The magnitude and direction of forces and velocities were considered as a function of penetration distance. This method used hole enlargement models, a rather simple method to calculate the momentum conservation of the two impacting bodies. Second method of Landkof and Goldsmith (1983) predicted petalling damage of a plate structure during penetration by using cylindro-conical projectile. This work showed that petalling damage is combination of bending and tearing process. Bending process was calculated due to the action of plastic hinges. The tearing process was formulated by Mode I fracture mechanics. Limitation of the method by Landkof and Goldsmith is in the calculation of all energies such as dishing, bending and tearing energy that was done independently. The third method, which was done recently by Wierzbicki (1999) and Lee (2004) gave a new method to describe petalling problem based on energy conservation. This method showed that tearing and bending process are related through the local radius of petal, while bending process and dishing process are related through the circumferential curvature of the dish. Tearing process was described more proper than before by using crack opening displacement (COD) criterion. In these works of Wierzbicki and Lee, there are some places which could be improved such as consideration of shearing process and modification of tearing model.